Impact of Cultural and Societal Factors on Stigma and Psychological Distress Experienced by Breast Cancer Patients in Abuja, Nigeria (Lafia Journal of Scientific and Industrial Research, 2025)
This study was carried out to evaluate the impact of cultural and societal factors on stigma and psychological distress experienced by breast cancer patients in Abuja, Nigeria. Structured questionnaires were administered to collate data on the significance of stigma and psychological distress on breast cancer patients, as well as risk factors and their impacts on breast cancer patients in Abuja. The Distress Thermometer (DT) of the National Comprehensive Cancer Network (NCCN) was used to evaluate distress, while the hospital anxiety and depression scale (HADS), was employed to evaluate emotional distress. A total of 348 respondents, comprising patients diagnosed with breast cancer aged 18 years and above in 2024, were considered for the study in three oncological centres in Abuja, Nigeria. Results of the study revealed that all respondents had experienced different forms of stigmatization due to their cancer status and lived with the feeling of being judged due to cancer, a total of 65.8% experienced discrimination from family and friends, 36.8% from strangers, 24.4% were discriminated by colleagues while 8.6% experienced discrimination from health workers. 44.5% of the respondents frequently experienced negative attitudes from people, 26.4% always had some forms of negative attitudes while 7.8% rarely experienced negative attitudes. The study established the prevalence of cancer care challenges such as stigmatization, cultural misconceptions, inadequate social and psychological support and limited access to medical services in healthcare centers in Abuja, Nigeria. Addressing these barriers requires a multi-faceted approach including public health education, expanded mental health services and improved healthcare infrastructure.